Effects of Communication, Financial Capability and Human Resource on Quality Service Delivery in Mission Hospitals: A Case of Meru County, Kenya - Mutunga , Stephen Laititi (Current Topics on Business, Economics and Finance Vol. 5, 2023)
This study aimed at establishing the effects of communication, financial capability and human resource in provision of quality service in mission hospitals in Meru County, Kenya. Communication is one of the most critical management practices in an organization. It is argued that managers spend over 70 percent of their time communicating. This is because without effective communication, understanding is lost or compromised in the ‘noise’ that characterizes everyday work life. Communication is effective if done well downwards, upwards and sideways from seniors, subordinates and peers respectively and effective feedback given. The means or channels of communication should also be very clear and short to avoid long routes that compromise the quality of what is being communicated. The health sector in Kenya is highly regulated by both the Government and relevant professional bodies to ensure quality is maintained in training of medical caregivers and in dispensing services. Three major categories of healthcare service providers exist in Kenya – public, private and mission/faith-based organizations with variants in between. The Kenyan Government is implementing a universal healthcare programme that hopes to provide quality and affordable healthcare for all citizens through insurance. This is an ambitious plan which calls for massive resources especially financial and human. In the past, post-colonial Kenya, mission hospitals were fully supported by foreign donors especially from Europe but the support has continuously declined over the years. The hospitals have resulted to cost sharing with clients (patients) for services to remain afloat. This has led to the mission hospitals designing various strategies for survival to remain competitive and offer quality services. However, the quality of service depends on how well the particular hospital or chain of hospitals manages their finances. Besides finances, prudent human resource management is at the core of every successful entity whether private, for profit, public, faith based and not-for-profit. The human resource is the driver of other resources towards organizational development and harmonization of service delivery. Meru County, one of the forty- seven counties in Kenya, is situated almost at the center of the country and has all the three categories of hospitals –public, private and mission ones. Within the mission hospitals in Meru County, besides the government and professional bodies, close regulation is also practiced by faith-based organizations that sponsor the hospitals. The purpose of this study was to establish the nature and effect of communication, sound financial management and human resource in providing quality service delivery in the mission hospitals in Meru County, Kenya. The study was formulated as a survey to cover all the eight mission hospitals namely Nkubu, Chaaria, Kiirua, Maua, Mutuati, Tigania, Igoji and Gitoro. Piloting was done at Wamba mission hospital in Isiolo county to ensure validity of study tools. Descriptive study design was used. Major stakeholders in the hospitals were targeted as respondents including CEOs, Human resource and public relations officers and other staff as internal stakeholders while patients, suppliers and neighbours formed external stakeholders. A total of 128 respondents were interviewed as a representative sample. A drop and pick method was used where questionnaires for each hospital were delivered and distributed to the potential respondents. Some respondents like patients and neighbours were assisted by researchers to fill in the questionnaires to avoid bothering them unnecessarily. Data was analyzed quantitatively using SPSS Version 23 and results described using descriptive statistics and presented in tables. The study found that communication had a significant positive affect on quality-of-service delivery (R=0.498, F=6.922, P=0.00) while financial capability of an individual hospital significantly affected quality of service (R= 0.537, F=10.72, P=0.00) and human resource correlated positively with quality service delivery in mission hospitals in Meru County (R=0.71, F=21.397, P=0.00). Effective communication and customer care was lauded as a critical consideration in dealing with clients and was emphasized among all levels of staff of mission hospitals to ensure sustainability of quality service while prudent financial management was not only critical for success in delivery of quality service but a necessary requirement if the hospitals were to sustain and grow their portfolios. Human resource was critical to organizational success in determining customer royalty and repeat visits through the quality of services offered by competent, committed and skilled staff that lead to positive word of mouth marketing of hospitals. The study recommended greater emphasis on effective communication with actionable feedback, prudent financial fidelity and improved customer care as well as improved human resource management for quality service to enable the hospitals retain and attract more clients. The study recommended further analysis of private and public hospitals on the same parameters for comparison as well as longitudinal studies to ensure replicability of findings.